2021
DOI: 10.1083/jcb.202003173
|View full text |Cite
|
Sign up to set email alerts
|

Zc3h10 regulates adipogenesis by controlling translation and F-actin/mitochondria interaction

Abstract: The commitment of mesenchymal stem cells to preadipocytes is stimulated by hormonal induction. Preadipocytes induced to differentiate repress protein synthesis, remodel their cytoskeleton, and increase mitochondrial function to support anabolic pathways. These changes enable differentiation into mature adipocytes. Our understanding of the factors that coordinately regulate the early events of adipocyte differentiation remains incomplete. Here, by using multipronged approaches, we have identified zinc finger CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 77 publications
(104 reference statements)
1
29
0
Order By: Relevance
“…The cytoskeleton is vital for determining and maintaining the shape and function of adipocytes, and depolymerization and repolymerization of actin affect both early adipogenesis and terminal differentiation 7,58 . Notably, reorganization of other cytoskeletal components has been shown to affect lipogenesis, mitochondrial activity, and glucose uptake in adipocytes [13][14][15]62,63 . MYH10 filaments were shown to undergo reorganization in a similar fashion to actin filaments 6 , with a stress-fiber-like appearance in preadipocytes, in contrast to the cortical distribution seen in differentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoskeleton is vital for determining and maintaining the shape and function of adipocytes, and depolymerization and repolymerization of actin affect both early adipogenesis and terminal differentiation 7,58 . Notably, reorganization of other cytoskeletal components has been shown to affect lipogenesis, mitochondrial activity, and glucose uptake in adipocytes [13][14][15]62,63 . MYH10 filaments were shown to undergo reorganization in a similar fashion to actin filaments 6 , with a stress-fiber-like appearance in preadipocytes, in contrast to the cortical distribution seen in differentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…More in-depth, proliferating mesenchymal stem cells (MSCs) show several F-actin stress fibers throughout the cell body. Upon addition of the adipogenic cocktail, F-actin moves toward the cell’s periphery, which begins to change its shape to a spherical appearance [ 72 ]. Factors that can regulate this process also have an impact on adipocyte differentiation.…”
Section: Novel Mechanisms Involved In Early Phases Of Adipogenesismentioning
confidence: 99%
“…An opposite situation appears when Zc3h10 is overexpressed. Zc3h10 overexpression enhances F-actin reorganization toward the cell periphery and stimulates lipid droplets formation [ 72 ]. In addition, it has been observed that actin organization also plays a key role in determining a discrete subpopulation of functional mitochondria, a key step towards mature adipocyte formation [ 72 ].…”
Section: Novel Mechanisms Involved In Early Phases Of Adipogenesismentioning
confidence: 99%
See 2 more Smart Citations